PERAN KOPERASI ANNISA DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA DI DESA PARUNGI KECAMATAN BOLIYOHUTO KABUPATEN GORONTALO - Sri Hantuti Paramata (Publik : (Jurnal Ilmu Administrasi), 2015)
The aim of this research was to know the role of Annisa cooperative in improving welfare of cooperative members and to determine the constraint members of Annisa cooperative in improving welfare in Parungi Village Sub-District of Boliyohuto Gorontalo Regency with using recording technique. The method of collecting the data is using descriptive qualitative method that is interview, observation, and documentation. To identification issues of welfare Annisa cooperative is using descriptive analytic to determine the position of a unit business strategies and also used of alternative strategies. Based on the results of research, analysis and presentation of the data about the role of Annisa Cooperative in improving welfare of its members can be summarized as follows: Annisa Cooperative has very large role in the life of members and efforts to improving welfare of its members. Cooperative face the constraint on the views of cooperative members and the cooperative development patterns, there has a social jealousy among the cooperative members, because of differences in income levels, in the case of education members often do not follow counseling, training, and education were held by cooperative, because the presence of competitors in terms of credit. Cooperatives should always consist in guiding on the principles, foundation, principles, and objectives in improving the welfare of cooperative member that become the members. And the cooperative also often hold counseling for the members of the cooperative in order can active to participate in cooperative education and changing patterns.